Encouraging Community Participation in Maintaining and Developing Kalibaru Village Infrastructure through Socialisation - Rustan, Fathur Rahman; Masgode, Muhammad Buttomi; Puspaningtyas, Retno; Hidayat, Arman; Dirgantara, Arya; Purnama, Haerul; La Ola, Mursalim Ninoy; Prasetyo, Bagus Eko; Mansyur, Mansyur; La Ode, Al Tafakur (Majalah Pengabdian Indonesia, 2024)
This study aimed to investigate the role of socialisation in promoting community participation in the maintenance and development of Kalibaru village infrastructure. A qualitative and case study approach was used to explore effective socialisation strategies in the context of rural infrastructure development in Indonesia, with a focus on Kalibaru village. The results of this activity show that socialisation programmes relevant to local needs and with a deep understanding of the community context can increase the active participation of the community in maintaining and developing Kalibaru village infrastructure. Factors such as the involvement of village officials, community awareness, and availability of resources also play an important role in the success of the socialisation programme. The recommendations include increasing community participation through more targeted and measurable socialisation strategies. Additionally, it is important to establish synergy between the community and the government in sustainable village development efforts.